Analisis Sebaran Genangan Banjir Menggunakan Pemodelan HECRAS-2D Terhadap Sosial Ekonomi dan Dampaknya terhadap Sosial Ekonomi di Bayongbong - Sulwan Permana; Sofa Tsuroya Aulya (Institut Teknologi Garut, 2026)
Flooding is a type of natural disaster influenced by weather conditions and high rainfall, and it remains a major problem in many regions, including Bayongbong District, Garut Regency. The steep topography on the slopes of Mount Cikuray increases the risk of surface runoff, leading to recurrent flooding during the rainy season. This study aims to design flood control measures by utilizing hydraulic modeling based on the HEC-RAS 2D software. The data used include rainfall, river discharge, and a Digital Elevation Model (DEM), which are analyzed using hydrological methods and hydraulic simulations. The hydrological analysis shows that the longer the return period, the greater the flood discharge and inundation. The maximum flood discharge for the 100-year return period reaches 450.9 m³/s, while the inundation volume is 35,563.96 m³. The inundation volume increases with each increase in the return period. Flooding causes significant socio-economic losses to the community. From a social perspective, floods result in housing damage and disruption of daily activities. From an economic perspective, flooding damages agricultural land and infrastructure and reduces community productivity.